Examining the Effect of Transformational Leadership on Employee Performance within Academic Organizations - Cut Fadhila Amal; Lailatussaadah (Al-Qalam Institue, 2026)
This study aims to examine the effect of transformational leadership on the performance of educational staff in a higher education institution. Employing a quantitative survey design, the research used a census technique in which all 44 members of the population were involved as respondents. Data were collected through structured questionnaires and analyzed using simple linear regression with IBM SPSS Statistics version 27. The findings reveal that transformational leadership has a positive and statistically significant effect on employee performance. The coefficient of determination (R Square) of 0.116 indicates that transformational leadership explains 11.6% of the variance in employee performance, while the remaining variance is influenced by other factors not examined in this study. These results suggest that the implementation of visionary, inspirational, and individually supportive leadership practices plays an important role in strengthening staff performance. Therefore, reinforcing transformational leadership behaviors can serve as a strategic approach to improving administrative effectiveness and overall organizational performance in higher education settings.